Interaksi Antara Masyarakat Suku Baduy dan Dunia Luar: Studi Kasus tentang Peran Eksternal dengan Praktik Budaya Lokal Desa Cepak Buah, Lebak, Banten - Gunawan, Syahrul; Fitriani, Fitriani (ArtComm : Jurnal Komunikasi dan Desain, 2025)
Cepak Buah Village is one of the traditional villages of the Baduy tribe which is one of the tourist destinations in Indonesia, along with the increasing number of tourism and the entry of technology, it is certainly directly proportional to the increasing interaction that occurs, this phenomenon provides intervention and causes a shift in the cultural habits of the local indigenous community. This study aims to explore the interactions that occur between the Baduy tribe and external culture. The method used in this study is qualitative with a case study approach. The results of this study found that the interactions that occur between the Baduy community of Cepak Buah Village continue to increase along with infrastructure development and the increasing number of tourists, cultural shifts occur on the side of the communication media used by the Cepak Buah community, the communication content discussed, language and habits that include social activities, economics and building architecture.